Analisis Kemampuan dalam Menyelesaikan Masalah Literasi Matematika Ditinjau dari Emotional Intelligence (EI) Siswa Kelas X - Dassa, Awi; Arwadi, Fajar; Damayanti, Isti Qama (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This study aims to describe the ability in mathematical literacy problems solving in terms of Emotional Intelligence (EI) of class X students of Senior High School 4 Maros. This research is qualitative research with a descriptive approach. The research subjects were taken purposively, namely 1 each from category of emotional intelligence. The instruments in this study is namely EI questionnaires, mathematical literacy tests, and interview guidelines. The indicators used consist of 6 levels of ability in solving PISA mathematical literacy problems according to the OECD. The results showed that: 1) Optimal category students are able to answer questions in a general context, addition to extracting relevant information, performed procedures applied simple problem-solving strategies, and conceptualized. 2) Special category students are able to answer questions in a general context, extract relevant information, carry out procedures sequentially, apply simple problem-solving strategies and conceptualize. 3) Vulnerable category students are able to answer questions in a general context, extract relevant information, carry out procedures sequentially, implement simple problem-solving strategies, and work effectively by involving assumptions. 4) Need alert category students are able to answer questions in a general context